Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Kecerdasan Spiritual Siswa Di Sma Pertiwi 1 Padang - Wilda Wahyuni; Indah Muliati (KOLONI, 2024)
This study focuses on the efforts of Islamic Education (PAI) teachers at SMA Pertiwi 1 Padang to enhance students' spiritual intelligence amidst the rapid development of digital technology in the era of Industry 5.0. The ease of access to information through social media platforms such as Instagram, TikTok, and Facebook has shaped a digital generation with diminished sensitivity due to their dependence on technology. This phenomenon presents significant challenges, particularly for individuals lacking a strong religious foundation, making them more susceptible to negative influences such as drug use, illegal racing, and other destructive behaviors. Through comprehensive and in-depth approaches, PAI teachers have successfully fostered positive changes in students' behavior and perspectives, demonstrating the effectiveness of these strategies in spiritual development. This study is a case study.